Studi Literatur: Model Pengembangan Rowntree sebagai Pendekatan dalam Pengembangan Bahan Ajar di Sekolah - Qonitah Zulfa Salsabila; Sri Marmoah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Teaching materials were an essential component in determining the quality of learning in elementary schools. However, many teachers were not yet able to develop teaching materials independently, which made the learning process rely heavily on textbooks or conventional resources. This study aimed to examine the application of the Rowntree development model as an approach to developing teaching materials in elementary schools. The research method used was a literature study, with data analyzed descriptively based on five relevant articles published between 2020-2025. The results show that teaching materials developed through the Rowntree model are valid, practical, effective, and capable of improving student learning outcomes. The model is also flexible for both printed and digital forms of materials. Therefore, the Rowntree model serves as a systematic approach for teachers to design innovative, engaging, and student-centered teaching materials in elementary schools.